2014
DOI: 10.1074/jbc.m114.582973
|View full text |Cite
|
Sign up to set email alerts
|

LL-37 Peptide Enhancement of Signal Transduction by Toll-like Receptor 3 Is Regulated by pH

Abstract: Background: How LL-37 delivers double-stranded RNA (dsRNA) to activate TLR3 signaling is poorly understood. Results: LL-37 was found to traffic to endosomes with RNA and releases the dsRNA upon endosome acidification. A peptide derived from LL-37 could antagonize LL-37⅐dsRNA trafficking. Conclusion: LL-37 trafficking of dsRNA is regulated by pH. Significance: This work establishes the mechanism of LL-37 enhancement of dsRNA-activated TLR3 signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 35 publications
(37 reference statements)
3
45
0
1
Order By: Relevance
“…However, studies on other endosomal TLRs and their ligands show the potential importance of endosomal degradation of cathelicidins. A recent report on activation of TLR3 by RNA-LL-37 complexes in epithelial cells indicated that interaction between LL-37 and RNA was lost during endosomal acidification (39). Although the stability of LL-37-RNA complexes at low pH are unclear (39,40), proteolytic breakdown could be the reason for the loss of RNA-LL-37 interaction and increased TLR3 activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies on other endosomal TLRs and their ligands show the potential importance of endosomal degradation of cathelicidins. A recent report on activation of TLR3 by RNA-LL-37 complexes in epithelial cells indicated that interaction between LL-37 and RNA was lost during endosomal acidification (39). Although the stability of LL-37-RNA complexes at low pH are unclear (39,40), proteolytic breakdown could be the reason for the loss of RNA-LL-37 interaction and increased TLR3 activation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report on activation of TLR3 by RNA-LL-37 complexes in epithelial cells indicated that interaction between LL-37 and RNA was lost during endosomal acidification (39). Although the stability of LL-37-RNA complexes at low pH are unclear (39,40), proteolytic breakdown could be the reason for the loss of RNA-LL-37 interaction and increased TLR3 activation. In addition, increased LPS uptake was detected in epithelial cells in the presence of LL-37 (41).…”
Section: Discussionmentioning
confidence: 99%
“…At acid pH, LL-37 is monomeric, at physiological pH cathecidin aggregates [37]. In the work of Singh, D. and coauthors (2014), it was found that the enhancement of LL-37 signal transduction by the Toll-like receptor 3 (TLR3) is regulated by pH [38]. Upon acidification by endosomes, the oligomerized LL-37 dissociates into LL-29 (a natural LL-37 fragment lacking the C-terminal part) [39], which is unable to transmit TLR3 signals [38].…”
Section: Resultsmentioning
confidence: 99%
“…In the work of Singh, D. and coauthors (2014), it was found that the enhancement of LL-37 signal transduction by the Toll-like receptor 3 (TLR3) is regulated by pH [38]. Upon acidification by endosomes, the oligomerized LL-37 dissociates into LL-29 (a natural LL-37 fragment lacking the C-terminal part) [39], which is unable to transmit TLR3 signals [38]. In this case, inhibition of cathepsins, which includes proteases, whose activity is activated by endosome acidification, resulted in an increase in the half-life of LL-37 from cells [38].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the cathelicidin precursor protein has also been found to facilitate nucleic acid associations with TLR in the endolysosome (43). LL-37 has been shown to bind dsRNA and traffic it to endosomes where it releases the dsRNA in a pH-dependent manner (44). Additionally, structural changes of LL-37⅐ligand complex were shown by electron microscopy illustrating that LL-37 and poly(I:C) individually formed globular structures, but a complex of the two formed filamentous structures (23).…”
Section: Discussionmentioning
confidence: 99%